Pearl from the Dragon's Mouth Evocation of Scene and Feeling in Chinese Poetry - Sun, Cecile C. C. (Michigan Monographs In Chinese Studies, 2020)
The interplay between the external world (ching) and the poet's inner world (ch'ing) lies at the heart of Chinese poetry, and understanding the interaction of the two is crucial to understanding this work from within its own tradition. Closely coordinating her discussions of poetry and criticism so that practice and theory become mutually enriching and illuminating, Sun offers sensitive and original readings of poems and a wealth of insights into Chinese poetics.